2003
DOI: 10.1007/s00592-003-0107-x
|View full text |Cite
|
Sign up to set email alerts
|

Patients? health education and diabetes control in a developing country

Abstract: We previously reported poor metabolic control in type 2 diabetic patients attending 2 primary care clinics in Trinidad. In an attempt to explain the poor metabolic control, we assessed primary care patients' theoretical knowledge of diabetes control and risk factors. Two hundred fifty-four diabetic out-patients recruited consecutively were asked by questionnaire: (i) if they were aware that family history of diabetes, obesity, physical inactivity and cigarette smoking were diabetes risk factors; (ii) if they k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…Having a close relative with chronic disease may be a good source of health information [20], [21], but such informal sources cannot be relied upon.…”
Section: Discussionmentioning
confidence: 99%
“…Having a close relative with chronic disease may be a good source of health information [20], [21], but such informal sources cannot be relied upon.…”
Section: Discussionmentioning
confidence: 99%
“…In Trinidad and Tobago, diabetic patients obtain their free medical supplies from pharmacies in the public sector and the medications are often similar across the board. Although there is a paucity of dieticians and diabetes health educators in most developing countries (Brackenridge, 1999), a research report has shown that patients who are knowledgeable in controlling diabetes do not often apply the theoretical knowledge in controlling their diabetes (Ezenwaka & Offiah, 2003). Thus, the present finding should be of some concern to the country given that a recent study in Results expressed as mean + SD.…”
Section: Discussionmentioning
confidence: 69%
“…31,32 Patient health education on lifestyle changes (physical activity, weight control, dietary habits) and self-monitoring of blood glucose are particularly challenging in developing countries. 44,45 However, there is reduction in long-term plasma glycemia and coronary heart disease risk profile when less educated and/or retired Caribbean T2DM patients were trained and supervised on self-monitoring of blood glucose. 46 It should be noted that this study did not apply statistical calculation to diagnose the number of patients with the metabolic syndrome based on the IDF definition.…”
Section: Discussionmentioning
confidence: 99%